2017
DOI: 10.1063/1.4973809
|View full text |Cite
|
Sign up to set email alerts
|

Electron radiation damage mechanisms in 2D MoSe2

Abstract: The contributions of different damage mechanisms in single-layer MoSe 2 were studied by investigating different MoSe 2 /graphene heterostructures by aberration-corrected high-resolution transmission electron microscopy (AC-HRTEM) at 80 keV. The damage cross-sections were determined by direct counting of atoms in the AC-HRTEM images. The contributions of damage mechanisms such as knock-on damage or ionization effects were estimated by comparing the damage rates in different heterostructure configurations, simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 20 publications
7
68
0
Order By: Relevance
“…Contrary to most metaldichalcogenides studied in the literature (Zan et al, 2013;Garcia et al, 2014;Lehnert et al, 2017) the SnS structure is quite stable during electron beam irradiation in the TEM even at 300 kV. This is to a large extent due to the larger thickness of the cross-sectional TEM specimens of the investigated flakes/crystallites compared to monolayers of metaldichalcogenides studied in-plane view TEM specimens.…”
Section: Electron Beam Damagementioning
confidence: 62%
“…Contrary to most metaldichalcogenides studied in the literature (Zan et al, 2013;Garcia et al, 2014;Lehnert et al, 2017) the SnS structure is quite stable during electron beam irradiation in the TEM even at 300 kV. This is to a large extent due to the larger thickness of the cross-sectional TEM specimens of the investigated flakes/crystallites compared to monolayers of metaldichalcogenides studied in-plane view TEM specimens.…”
Section: Electron Beam Damagementioning
confidence: 62%
“…1d shows an enlarged image of the area marked with a red square in Fig. 1b, where some double sulfur vacancies typically present in the ML MoS 2 samples [29,[45][46][47], can be recognized.…”
Section: Optimized Growthmentioning
confidence: 99%
“…25 single-layer TMDs have shown that electron beam-induced damage can lead to rapid generation of structural defects through other mechanisms, which include electronic excitations, especially for insulating materials, and beam-induced chemical etching. 26,27 The effects of electron beam-induced damage can be reduced by protecting the single-layer TMD with one graphene layer or sandwiching it between two graphene layers. [27][28][29] Here, we investigate the single-layer 1T-TaSe 2 /graphene heterostructure.…”
mentioning
confidence: 99%
“…26,27 The effects of electron beam-induced damage can be reduced by protecting the single-layer TMD with one graphene layer or sandwiching it between two graphene layers. [27][28][29] Here, we investigate the single-layer 1T-TaSe 2 /graphene heterostructure. Furthermore, we assume that heating of a few-layer thick sample by the electron beam at 80 kV can be neglected, as experiments and theory indicate.…”
mentioning
confidence: 99%